The Effects of 1 Egg per Day on Iron and Anemia Status among Young Malawian Children: A Secondary Analysis of a Randomized Controlled Trial. Issue 6 (13th May 2022) - Werner, E Rochelle; Arnold, Charles D; Caswell, Bess L; Iannotti, Lora L; Lutter, Chessa K; Maleta, Kenneth M; Stewart, Christine P
ABSTRACT: Background: Young children with diets lacking diversity with low consumption of animal source foods are at risk of iron deficiency anemia (IDA). Objectives: Our objectives were to determine the impact of supplementing diets with 1 egg/d on 1 ) plasma ferritin, soluble transferrin receptor (sTfR), body iron index (BII), and hemoglobin concentrations and 2 ) the prevalence of iron deficiency (ID), anemia, and IDA. Methods: Malawian 6–9-mo-old infants in the Mazira trial (clinicaltrials.gov; NCT03385252) were individually randomly assigned to receive 1 egg/d for 6 mo ( n = 331) or continue their usual diet ( n = 329). In this secondary analysis, hemoglobin, plasma ferritin, sTfR, C-reactive protein (CRP), and α-1-acid glycoprotein (AGP) were measured at enrollment and 6-mo follow-up. Iron biomarkers were corrected for inflammation. Ferritin, sTfR, BII, and hemoglobin were compared between groups using linear regression. Prevalence ratios (PRs) for anemia (hemoglobin <11 g/dL) and ID (ferritin <12 µg/L, sTfR >8.3 mg/L, or BII <0 mg/kg) between groups were compared using log binomial or modified Poisson regression. Results: A total of 585 children were included in this analysis (Egg: n = 286; Control: n = 299). At enrollment, the total prevalence of anemia was 61% and did not differ between groups. At 6-mo follow-up, groups did not differ in geometric mean concentration of hemoglobin [mean (95% CI); Egg: 10.9 (10.7, 11.1) g/dL; Control: 11.1 (10.9, 11.2) g/dL] and inflammation-adjusted ferritin [Egg: 6.52 (5.98, 7.10) µg/L; Control: 6.82 (6.27, 7.42) µg/L], sTfR [Egg: 11.34 (10.92, 11.78) mg/L; Control: 11.46 (11.04, 11.89) mg/L] or BII [Egg: 0.07 (0.06, 0.09) mg/kg; Control: 0.07 (0.05, 0.08) mg/kg]. There were also no group differences in anemia [Egg: 46%; Control 40%; PR: 1.15 (95% CI: 0.96, 1.38)], ID [PR: 0.99 (0.94, 1.05)], or IDA [PR: 1.12 (0.92, 1.36)]. Conclusions: Providing eggs daily for 6 mo did not affect iron status or anemia prevalence in this context. Other interventions are needed to address the high prevalence of ID and anemia among young Malawian children. This trial is registered at http://www.clinicaltrials.gov as NCT03385252. Abstract : The egg intervention did not impact children's iron status or prevalence of anemia. Young children in rural Malawi remain at high risk of iron deficiency and anemia.